2020
DOI: 10.3390/geosciences10080322
|View full text |Cite
|
Sign up to set email alerts
|

Open-Source MASW Inversion Tool Aimed at Shear Wave Velocity Profiling for Soil Site Explorations

Abstract: The shear wave velocity profile is of primary interest for geological characterization of soil sites and elucidation of near-surface structures. Multichannel Analysis of Surface Waves (MASW) is a seismic exploration method for determination of near-surface shear wave velocity profiles by analyzing Rayleigh wave propagation over a wide range of wavelengths. The inverse problem faced during the application of MASW involves finding one or more layered soil models whose theoretical dispersion curves match the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Considering the non-linearity and non-convexity of the inverse problem, a Mente Carlo-based global search method is used to potentially escape from being stuck at the local minimum. Detailed description of the software used in this study can be found in Olafsdottir et al (2018) and Olafsdottir et al (2020).…”
Section: Multichannel Analysis Of Surface Waves For Shear Wave Veloci...mentioning
confidence: 99%
“…Considering the non-linearity and non-convexity of the inverse problem, a Mente Carlo-based global search method is used to potentially escape from being stuck at the local minimum. Detailed description of the software used in this study can be found in Olafsdottir et al (2018) and Olafsdottir et al (2020).…”
Section: Multichannel Analysis Of Surface Waves For Shear Wave Veloci...mentioning
confidence: 99%
“…For instance, the largest wavenumber, hence the lowest phase velocity, for a frequency belongs to the fundamental mode, and the second largest wavenumber belongs to the second mode. An open-source software, MAS Waves [27] has included a function (MASWaves_theoretical_dispersion_curve.m) to compute the fundamental-mode dispersion curve in terms of wavelength vs. phase velocity, which was used in this study.…”
Section: Theoretical Dispersion Curvementioning
confidence: 99%
“…The common methods used in the inversion analysis of surface waves include iterative techniques such as least-squares fitting and direct search algorithms, which aim to find the parameters that best fit the experimental data. Recent developments in inversion analysis include the use of Levenberg-Marquardt method [6], genetic algorithm [7], neighborhood algorithm [8], simulated annealing [9], artificial bee colony algorithm [10], Monte Carlo search technique [11], deep-Q network search algorithm [12], and particle swarm optimization [13].…”
Section: Introductionmentioning
confidence: 99%